Reskilling and Upskilling Strategies as the Key to Workforce Adaptation in the Era of Automation and AI - Masriadi Masriadi; Marhati Marhati; Jumiati Jumiati; Abdul Sahid; Sahruddin Malik (PERSPEKTIF, 2025)
The transformation of the labor landscape driven by automation and artificial intelligence (AI) demands new, relevant, and adaptive skills from the workforce. This study aims to identify contextual and inclusive reskilling and upskilling strategies in rural areas, focusing on Bone Regency, South Sulawesi. Using a qualitative case study approach with in-depth interviews involving training providers, participants, community leaders, and local government agencies, the study finds that strengthening basic digital literacy is a critical foundation for preparing communities to navigate technological transitions. Blended learning models, the use of locally relevant media, and the involvement of community mentors have proven effective in increasing participation and comprehension. However, challenges such as limited digital infrastructure, a shortage of qualified trainers, and low training literacy persist. Multi-stakeholder collaboration among vocational training institutions, village governments, and local businesses emerges as a key strategy to expand training reach and ensure program sustainability. Locally relevant training, such as digital marketing for SMEs and online modules aligned with the national Prakerja program, shows strong potential to create new employment opportunities and enhance community competitiveness. This study recommends strengthening training infrastructure, providing continuous mentoring, and designing community-based policies as essential strategies for successful workforce transformation in the digital era. The findings contribute to Indonesia’s national human resource development agenda by offering evidence-based insights on how localized, collaborative approaches can accelerate workforce adaptation to global technological disruption.